Optically Active Telecom Defects in MoTe2 Fewlayers at Room Temperature - Yuxin Lei; Qiaoling Lin; Sanshui Xiao; Juntao Li; Hanlin Fang (Nanomaterials, 2023)
The optical and electrical properties of semiconductors are strongly affected by defect states. The defects in molybdenum ditelluride (MoTe<semantics>2</semantics>) show the potential for quantum light emission at optical fiber communication bands. However, the observation of defect-related light emission is still limited to cryogenic temperatures. In this work, we demonstrate the deep defect states in MoTe<semantics>2</semantics> fewlayers produced via a standard van der Waal material transfer method with a heating process, which enables light emission in the telecommunication O-band. The optical measurements show evidence of localized excitons and strong interaction among defects. Furthermore, the optical emission of defects depends on the thickness of the host materials. Our findings offer a new route for tailoring the optical properties of two-dimensional materials in optoelectronic applications.